2021
DOI: 10.3389/fpls.2021.627865
|View full text |Cite
|
Sign up to set email alerts
|

Research and Application of Several Key Techniques in Hyperspectral Image Preprocessing

Abstract: This paper focuses on image segmentation, image correction and spatial-spectral dimensional denoising of images in hyperspectral image preprocessing to improve the classification accuracy of hyperspectral images. Firstly, the images were filtered and segmented by using spectral angle and principal component analysis, and the segmented results are intersected and then used to mask the hyperspectral images. Hyperspectral images with a excellent segmentation result was obtained. Secondly, the standard reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…This section performs the detailed survey on segmentation approaches. There are three different categories of segmentation approaches are used, pixel-level segmentation [15], object-level segmentation [16], and sub-pixel segmentation or unmixing [17]. The choice of approach depends mainly on the application requirement since they offer both advantages and limitations.…”
Section: Related Workmentioning
confidence: 99%
“…This section performs the detailed survey on segmentation approaches. There are three different categories of segmentation approaches are used, pixel-level segmentation [15], object-level segmentation [16], and sub-pixel segmentation or unmixing [17]. The choice of approach depends mainly on the application requirement since they offer both advantages and limitations.…”
Section: Related Workmentioning
confidence: 99%
“…In the original data, there is a lot of signal noise and drift in the spectral signal. All three preprocessing methods can eliminate random noise in the spectral signal and improve the signal-to-noise ratio of the sample signal (Li et al, 2021).…”
Section: Spectral Preprocessingmentioning
confidence: 99%
“…The authors also observed that increasing the patch size, leads to improvements in performance, indicating the benefits of using the spatial information around pixels for deep learning based classifiers compared to linear models. In a recent work [15], the authors introduce HS image segmentation, correction and spectral-spatial denoising as HS image pre-processing to improve the HS image classification accuracy.…”
Section: Related Workmentioning
confidence: 99%